Castor oil based eco-friendly lubricating oil additives. Issue 5 (9th April 2021) - Hoque, Mainul; Paul, Sujan; Ghosh, Pranab
Abstract: The application of vegetable oil based additive for lubricating oil has attracted considerable interest due to their biocompatibility and multifunctional performances compared to conventional additives. In the present work, we have synthesized homopolymer of castor oil and copolymer of castor oil with styrene by thermal method without any solvent at different percentage composition by using BZP (benzoyl peroxide) as initiator. Characterization of the additives was completed by spectral technique (FT-IR and NMR spectroscopy). The molecular weight of the prepared additives was determined by gel permeation chromatography method (GPC method). Thermo gravimetric analysis (TGA) method was used to study the thermal stability of the prepared polymers. Standard ASTM methods were used to investigate the performance of all the prepared polymers in SN150 mineral oil as viscosity index improver (VII), pour point depressant (PPD) and antiwear. Biodegradability of all the polymers was determined disk diffusion method. From the experimental results, it was found that copolymers are more effective as VII, PPD and antiwear than homopolymer. Moreover, average molecular weight, thermal stability and performances as VII and antiwear increase with increasing the percentage of styrene in copolymers. Graphical Abstract: